IMPLEMENTASI KEBIJAKAN PUBLIC PRIVATE PARTNERSHIP (PPP) DALAM MENINGKATKAN INFRASTRUKTUR RISET DI INDONESIA - Zaidan Aulia Wicaksono; Nia Karniawati (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2023)
Through various financing plans, including the Public Private Partnership (PPP), the government continues to encourage infrastructure development. With this method, the private sector is urged to participate in infrastructure development so as to ease the government's burden. As a government institution engaged in research, the National Research and Innovation Agency (BRIN) formerly the Indonesian Institute of Sciences (LIPI) has chosen the PPP scheme for the Management and Development of the National Research Ship Fleet to increase the capacity of research vessels. research infrastructure. Using a literature study approach and relevant policy and regulatory literature, this report is prepared as a descriptive qualitative investigation. A summary of potential income and risk analysis of the PPP project is also presented along with an explanation of the need for research infrastructure, in this case research vessels in Indonesia. The output of this study also offers a summary of PPP implementation procedures at BRIN. This can cover the topic of whether the PPP plan is for the development of PPP-type research infrastructure, whether the process is solely geared towards commercial interests, how risk sharing is carried out in a PPP, and how BRIN implements the PPP.